Web-Enhanced Tobacco Tactics With Telephone Support Versus 1-800-QUIT-NOW Telephone Line Intervention for Operating Engineers: Randomized Controlled Trial - Choi, Seung Hee; Waltje, Andrea H; Ronis, David L; Noonan, Devon; Hong, OiSaeng; Richardson, Caroline R; Meeker, John D; Duffy, Sonia A (JMIR Publications, 2014)
BackgroundNovel interventions tailored to blue collar workers are needed to reduce the disparities in smoking rates among occupational groups. ObjectiveThe main objective of this study was to evaluate the efficacy and usage of the Web-enhanced "Tobacco Tactics" intervention targeting operating engineers (heavy equipment operators) compared to the "1-800-QUIT-NOW" telephone line. MethodsOperating engineers (N=145) attending one of 25 safety training sessions from 2010 through 2012 were randomized to either the Tobacco Tactics website with nurse counseling by phone and access to nicotine replacement therapy (NRT) or to the 1-800-QUIT-NOW telephone line, which provided an equal number of phone calls and NRT. The primary outcome was self-reported 7-day abstinence at 30-day and 6-month follow-up. The outcomes were compared using chi-square tests, t tests, generalized mixed models, and logistic regression models. ResultsThe average age was 42 years and most were male (115/145, 79.3%) and white (125/145, 86.2%). Using an intent-to-treat analysis, the Tobacco Tactics website group showed significantly higher quit rates (18/67, 27%) than the 1-800-QUIT NOW group (6/78, 8%) at 30-day follow-up (P=.003), but this difference was no longer significant at 6-month follow-up. There were significantly more positive changes in harm reduction measures (quit attempts, number of cigarettes smoked per day, and nicotine dependence) at both 30-day and 6-month follow-up in the Tobacco Tactics group compared to the 1-800-QUIT-NOW group. Compared to participants in the 1-800-QUIT NOW group, significantly more of those in the Tobacco Tactics website group participated in the interventions, received phone calls and NRT, and found the intervention helpful. ConclusionsThe Web-enhanced Tobacco Tactics website with telephone support showed higher efficacy and reach than the 1-800-QUIT-NOW intervention. Longer counseling sessions may be needed to improve 6-month cessation rates. Trial RegistrationClinicaltrials.gov NCT01124110; http://clinicaltrials.gov/ct2/show/NCT01124110 (Archived by WebCite at http://www.webcitation.org/6TfKN5iNL).